Valuing freedom of expression at the expense of linguistic aspect: The analysis of Kaur's selected poems - Lestari, Dewi Puspa; Alamsyah, Aam (Journal of Language, Literature, Social and Cultural Studies, 2024)
As a well-known poet, Rupi Kaur has written several poems which attract worldwide accolades. The present study explores several important aspects of her selected poems, such as feminism, humor, and irony. It was conducted qualitatively. In this case, the researchers acted to analyze and collected the data consecutively. The findings indicated that the concepts of feminism described in her poems tend to be more liberal and radical. The use of crude language to depict women as "male objects" plainly supports this notion. Furthermore, Kaur employs filthy language to prick the reader's conscience and make them aware of the societal critique offered in her poems. The element of Humor identified in the poems is used to portray the injustice of societal rules that restrict women. Despite showing poor grammatical aspects, such as the use of proper subject, the poem strives to vividly criticize the role of women, which is commonly valued solely on their physical looks, dismissing their worth and complexity as humans.